2023
DOI: 10.31219/osf.io/vmcng
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Through Their Eyes and In Their Shoes: Providing Group Awareness During Collaboration Across Virtual Reality and Desktop Platforms

Abstract: Many collaborative data analysis situations benefit from collaborators utilizing different platforms. However, maintaining group awareness between team members using diverging devices is difficult, not least because common ground diminishes. A person using head-mounted VR cannot physically see a user on a desktop computer even while co-located, and the desktop user cannot easily relate to the VR user’s 3D workspace. To address this, we propose the “eyes-and-shoes” principles for group awareness and abstract th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Within the studies we analyse, it is evaluated using observations, qualitative interviews, custom questionnaires and Thinking Aloud protocols, see Table 5. While collaboration has been described as an integral part of IA [EBC*21], we found only a relatively small number of studies on collaboration in our analysis (15/231), similar to Saffo et al [SBDE23] and Dey et al [DBLS18].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Within the studies we analyse, it is evaluated using observations, qualitative interviews, custom questionnaires and Thinking Aloud protocols, see Table 5. While collaboration has been described as an integral part of IA [EBC*21], we found only a relatively small number of studies on collaboration in our analysis (15/231), similar to Saffo et al [SBDE23] and Dey et al [DBLS18].…”
Section: Resultssupporting
confidence: 87%
“…Research Transparency : To improve transparency and quality of the research, preregistration of studies is becoming increasingly popular in user studies, which is also a trend we found in our analysis [YTHL22, SGBI22, SBDE23, WBR*20, YCB*21, BCC*20, DUWW22, LPED20]. Therefore, researchers submit details on their planned study to an online registry.…”
Section: Discussion and Future Workmentioning
confidence: 84%
“…Although we found that asymmetric collaboration is feasible, a longitudinal study with more participants could be ideal for more profound insights. Moreover, more studies are needed to investigate the effect beyond performance, communication, and preference, such as group awareness [48]. In addition, we did not investigate VR-VR in our second study due to the variance in participants' VR experience and the duration limitation.…”
Section: Discussionmentioning
confidence: 99%
“…In immersive analytics, brushing and linking have seen (arguably limited) use, be it to compare multiple immersive coordinated views [AWG*15,LPED20] or to support collaborative awareness [LHC*21, SBDE23, SS22]. Most methods use simple 3D selection techniques (e.g., raycasting) or pure 2D selection techniques (e.g., touchscreen inputs).…”
Section: Related Workmentioning
confidence: 99%